Update membranous nephropathy - Hoxha, Elion; Huber, Tobias B (Deutsche medizinische Wochenschrift (1946), 2020)
Membranous nephropathy is an autoimmune disease caused in most cases by binding of circulating antibodies to antigens on podocytes. PLA R1 and THSD7A have been identified as target antigens in 70-80 % and 2-3 % of patients, respectively. The detection of PLA R1- and THSD7A-antibodies in the blood and staining of renal biopsies for the respective antigens allow the correct diagnosis of PLA R1- and THSD7A-associated membranous nephropathy, respectively, in practically 100 % of cases. Measurement of PLA R1- and THSD7A-antibodies is helpful in order to further individualize the decision whether to perform a renal biopsy in patients with suspected membranous nephropathy. PLA R1-antibody level is a strong predictor for remission of proteinuria, loss of renal function and relapse of disease. Moreover, treatment decisions in patients with PLA R1-associated MN are increasingly based on the PLA R1-antibody levels. Rituximab was shown to be non-inferior to ciclosporine A to induce remission of proteinuria after 12 months. After 24 months rituximab was superior to ciclosporine A for the same endpoint. Development of novel treatment strategies, focusing on disease pathogenesis, remains highly relevant for these patients.